2022
DOI: 10.3390/ijerph19042297
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Amyloidosis in a Coal Miner with Silicosis: Is Exposure to Silica Dust a Cause of Amyloid Deposition?

Abstract: The over-secretion of monoclonal immunoglobulin light chains by clonal B cells followed by the aggregation and extracellular deposition of fibrillar deposits are responsible forthe clinical course AL amyloidosis. It is well documented that silica significantly increases the number of immunoglobulin-secreting cells. In the present paper, we report on a coal miner with silicosis and fast progressing primary amyloidosis with predominantly heart, kidney, and lung manifestations. Severeheart failure due to myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…RCS exposure can also lead to lung cancer (IARC 1997 ), pneumoconiosis (Hua et al 2018 ), tuberculosis, chronic bronchitis, emphysema, and chronic obstructive pulmonary disease (Mason and Thompson 2010 ). RCS is a significant risk factor for developing immunologic and autoimmune diseases such as chronic renal disease (Steenland et al 2001 ), monoclonal gammopathy and amyloidosis (Gołębiowski et al 2022 ), Sjogren’s syndrome (Ziebelman et al 2022 ), scleroderma (Haustein et al 1990 ), rheumatoid arthritis, systemic lupus erythematosus, and sarcoidosis (Mason and Thompson 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…RCS exposure can also lead to lung cancer (IARC 1997 ), pneumoconiosis (Hua et al 2018 ), tuberculosis, chronic bronchitis, emphysema, and chronic obstructive pulmonary disease (Mason and Thompson 2010 ). RCS is a significant risk factor for developing immunologic and autoimmune diseases such as chronic renal disease (Steenland et al 2001 ), monoclonal gammopathy and amyloidosis (Gołębiowski et al 2022 ), Sjogren’s syndrome (Ziebelman et al 2022 ), scleroderma (Haustein et al 1990 ), rheumatoid arthritis, systemic lupus erythematosus, and sarcoidosis (Mason and Thompson 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amyloids can accumulate not only in brain but also in different tissues and body organs that result in clinical syndromes [ 17 ]. A recent study has shown multiorgan amyloidosis in a coal miner [ 22 ]. In a Swedish study on amyloidosis, all of the 33 cases had simultaneous pulmonary and cardiac involvements [ 5 ].…”
Section: Introductionmentioning
confidence: 99%